2017
DOI: 10.2991/emcm-16.2017.131
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Phonics Instruction on Pre-school Learners' Development in English Language Course

Abstract: Abstract. Phonics is one important part of language learning and it contributes to language literacy through involving learners understanding the relationship between letter form and speech sound. It's made evident that younger learners are shown the ability to learn a foreign language in many researches and thereby phonics should be taught systematically as part of a balanced and integrated English language program. It's found that the impact of phonics instruction on development of pre-school English languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Implementasi metode fonik ini sebenarnya sudah ada sejak dulu dan hingga saat ini masih menjadi salah satu metode alternatif dalam pembelajaran Bahasa Inggris pada anak usia dini. Manfaat dari pengenalan fonik dalam pembelajaran Bahasa Inggris bagi anak usia dini adalah perkembangan bahasa, seperti pengucapan kata, pengejaan yang tepat, pembendaharaan kata yang berkembang, dan kemampuan membacanya pun akan berkembang dengan baik (Ren and Ma, 2017).…”
Section: Pendahuluanunclassified
“…Implementasi metode fonik ini sebenarnya sudah ada sejak dulu dan hingga saat ini masih menjadi salah satu metode alternatif dalam pembelajaran Bahasa Inggris pada anak usia dini. Manfaat dari pengenalan fonik dalam pembelajaran Bahasa Inggris bagi anak usia dini adalah perkembangan bahasa, seperti pengucapan kata, pengejaan yang tepat, pembendaharaan kata yang berkembang, dan kemampuan membacanya pun akan berkembang dengan baik (Ren and Ma, 2017).…”
Section: Pendahuluanunclassified
“…Initially, since the children did not know how to read and were unable to utter a single word, the researchers decided to begin teaching the children with the letter sounds or phonics. Phonics is an integral aspect of language learning because it allows learners to understand the connection between letter type and speech tone, which leads to language literacy (Ren & Ma, 2017). Also, learning more about phonics assists learners to read more quickly and recite what they've just read out (Carley, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is a global trend toward the incorporation of phonics in EFL instruction among young English language learners [1]. It's suggested that that young EFL learners are shown the ability to learn a foreign language, and phonics are supposed to be taught systematically as part of a balanced and integrated English language program among EFL learners including Chinese young children [2]. How much do you know about the effectiveness and efficiency of phonics learning among Chinese school-age children?…”
Section: Introductionmentioning
confidence: 99%